Penggunaan Metode Bermain Word-Grouping Dan Whispering Untuk Meningkatkan Penguasaan Nursing Vocabulary Pada Siswa Di Smk Kesehatan Bali Medika Denpasar - Ni Kadek Ary Susandi; Rusanti, Putu; Galuh Wismadewi, I Gusti Agung; Novi Suryati, Ni Wayan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
English language learning in vocational schools aims to provide students with language skills that can maximally support the competence of the specific field of expertise that students have. However, English teaching in many vocational schools, such as the Bali Medika Health Vocational School, is not designed as English for Specific Purposes (ESP), thus found to be insufficient to equip students to communicate using English in their target career. In addition, the teachers at this school revealed that it is difficult to find the kind of activities that can be organized to make learning English interesting and to choose material that is suitable to the needs of students as a future nurse assistant. Therefore, an innovative learning activity is needed to assist teachers in delivering teaching material that is suitable and relevant to the student’s target career. Learning through games such as word grouping and whispering was organized in the class to teach students the specialized nursing vocabulary. At the evaluation, students reported that learning nursing vocabulary through word-grouping and whispering activities was fun, and they could understand the material well. The learning activities helped them enrich their nursing vocabularies and they were very satisfied with the English learning in this program. Keywords: ESP, games, nursing vocabulary, word-grouping, whispering.